Italian-Spanish Contact in Early 20th Century Argentina - Ennis, Juan Antonio (2015)
This article attempts to provide a general approach to the exceptional language contact situation that took place in Argentina from the end of the 19th century until the first decades of the 20th century, in which an enormous immigration flow drastically modified the sociolinguistic  landscape. This was most evident in urban environments?and among them especially the Buenos Aires area?and led the local ruling elites to set up a complex and massive apparatus for the nationalisation of the newcomers, which included a language shift in the first stage. Given that the majority of immigrants came from Italy, the most widespread form of contact was that between the local varieties of Spanish and the Italian dialects spoken by the immigrants, which led to the creation of a contact variety called Cocoliche that arose, lived then perished. Although this contact variety did not survive the early years, at least not as a full-fledged variety, the history of its emergence and the ways in which it can be studied today nevertheless make it an object of special interest for research perspectives oriented around the question of the early years of language contact. This article gives an account of this history so as to provide an analysis of a series of documents that, in a highly mediated way, can be used as an unreliable but nonetheless interesting corpus for the study of language and culture contact.